Downstream lightening and upward heavying: Experiments with sediments differing in density. Issue 5 (23rd March 2015) - Viparelli, Enrica; Solari, Luca; Hill, K. M.; Mohrig, David
Abstract Sorting and selective transport of particles by material density is important for understanding a wide range of processes, including the formation of mineral placers, deposition of mine tailings and routing of tracers and contaminants. This article describes an experimental study of the transport of mixtures of particles of differing density in a sediment‐feed flume. During the runs, a downstream prograding wedge‐shaped deposit was formed. Results show two sorting processes: (i) longitudinal sorting characterized by preferential deposition of heavy particles in the upstream part of the deposit – downstream lightening; and (ii) vertical sorting with less dense particles preferentially deposited in the lowermost portion of the migrating front – upward heavying. Downstream lightening is the analogue of the well‐known downstream fining observed in the more studied case of mixtures of heterogeneous size with the same density. In both cases, the lighter particles are carried further downstream than the heavier particles. Upward heavying is unexpected when compared with deposits of heterogeneous size and same‐density particles, where the heaviest (i.e. coarsest) particles are deposited in the lowermost part of the front. The physical mechanism underlying this upward heavying might be related to the physics of gravity‐driven granular flows; the front of the deposit acts like a dense granular flow down an inclined plane. In this case, the denser particles settle away from the free surface and at the top of the heap, while the lighter particles flow to the bottom. As the front of the deposit advances, this progressively gives rise to an upward heavying pattern. The application of classical surface‐based fractional bedload transport models suggests that equal mobility is not approached in the case of mixtures of particles with uniform size and different densities. This study hypothesizes that other mechanics related to the physics of the segregation processes in these systems contribute to these results.